THE RELATIONSHIP OF MONETARY POLICY TO THE STOCK MARKET: THE EXPERIENCE WITH MARGIN REQUIREMENTS* - Bolster, Richard L. (Journal of Finance, 1967)
Source: Dissertation Abstracts International, Volume: 27-05, Section: A, page: 1181.